Positive impacts of a covered veranda on broiler chicken welfare - F. Mocz; J-P. Moysan; L. Warin; A. Keita; V. Michel; M. Guinebretière (Poultry Science, 2025)
In standard broiler production systems, birds do not have outdoor access and spend their entire lives in the same environment. A covered veranda can improve broilers’ living conditions by providing access to different environments and to areas with varying space availability (i.e. different stocking densities), while also allowing them to experience outdoor sensory stimulations and protecting them from predators and the risk of disease. This study aimed to evaluate the welfare and health of broilers with access to a covered veranda. Redbro broilers were randomly assigned to six identical enriched rooms (with elevated platform and alfalfa bales), each containing 2,478 birds (final stocking density of 26 kg/m²). Three rooms had access to a covered veranda from 22 days of age (D22), while the other three had no such access (control). Footpad dermatitis, hock burns and gait were assessed on D36. We also measured activity levels (D34 and D37), use of the covered veranda (from D22 to slaughter), litter quality (D34 and D37), as well as feed and water consumption throughout the rearing period. Mortality and body weight were also monitored. Access to a covered veranda did not affect mortality, body weight, litter quality, or feed and water consumption. None of the broilers from either treatment group exhibited gait issues or footpad dermatitis. However, the prevalence of hock burns was lower in the broilers having access to a covered veranda. Additionally, more active behaviors were observed among broilers from the covered veranda group than from the control group. The covered verandas were frequently used, with usage increasing as the broilers aged. Within a day, use was more frequent in the morning and decreased thereafter. Providing access to a covered veranda improved bird welfare without negatively impacting zootechnical indicators.